Uma sequência didática para o ensino de máquinas térmicas no ensino médio - FERREIRA, Gabriel Felipe Furtado (2020)
The present work presents a didactic sequence for the teaching of thermal machines, using as its thematic axis the history of science and the machines used by contemporary society. The development of the work was based on the David Ausubel work on meaningful learning as well as the use of conceptual maps proposed by Joseph Novak and the Potentially Significant Teaching Units of Marco Antonio Moreira. The sequence features a total of eight encounters in which various teaching tools are used, such as the use of videos, experiments carried out in the classroom, scientific texts and a field visit in a thermoelectric plant. The purpose of this work is for the student to realize the importance of thermal machines for the development of modern society and the dependence we have of these machines, in the current time, starting from the transportation means equipped with internal combustion engines until the generation of electric energy in the thermoelectric and thermonuclear plants. The proposal will be applied in the second grade of the high school, CE Humberto de Campos School in São Luís do Maranhão.